Preliminary Prediction of Biodiesel From Used Cooking Oil As Electricity Use DKI Jakarta - Adji, Muhammad Wahyu Fattiar; Putri, Cyntia Aulia; Nabila, Dhian; Erlingga, Falia Ayu; Suryawan, I Wayan Koko; Sarwono, Ariyanti; Maharani, Lisa; Muhammad, Umardimas Mumtaz; Aprill, Gregorius De; Oktaviani, Namira Yostya; Putri, Gabriella Natasya; Syaifaurrahmah, Syaifaurrahmah; Fansyah, Delfia; Yuliani, Aulia Rachmah (Universitas Islam Lamongan, 2022)
Biodiesel is a biodegradable fuel made from vegetable oils and animal fats processed by chemical reactions involving catalysts and alcohol. This study aims to determine the occurrence of cooking oil waste produced by residents of DKI Jakarta, to know the average electricity usage of residents in Jakarta, to find out whether the biodiesel produced can meet the electricity needs of every household in DKI Jakarta. The method used in this research is the quantitative method. Primary and secondary data are used to support the paper. Primary data was used from questionnaires distributed to residents of DKI Jakarta, and secondary data used for this paper are literature studies obtained from relevant books, journals, and research. The waste of used cooking oil generated by DKI Jakarta residents is 1,249 L/household/month.